PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI, SISTEM PELAPORAN, DAN DESENTRALISASI TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SKPD BENGKALIS) - Putra, Boby Arona; Hasan, Amir; Yasni, Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose ofthis study was toobserve the effect ofbudget goal clarity, accounting controls, reporting systems, and decentralization on performance accountability ofgovernment agencies. The sample inthis study wasthe head of the finance department dina and work units. Methods of data analysis using multiple linear regression. Based on the research results, obtained t value variable budget goal clarity at 2.482 and 0.018 significance. Thus, the t (2.482) > t table (2.024) and significance (0.018) < 0.05. It means that the budget goal clarity affect the performance accountability of government agencies. Then obtained t value accounting control variables at 0.423 and 0.675 significance. Thus, the t (0.423) < t table (2.024) and significance (0.675) > 0.05. Meaning that accounting control does not affect the performance accountability of government agencies. Subsequently obtained t value of 2.119 reporting system variables and significance of 0.041. Thus, the t (2.119) > t table (2.024) and significance (0.041) < 0.05. It means reporting system affect the performance accountability of government agencies. And obtained the decentralization variable t value of 2.563 and 0.014 significance. Thus, the t (2.563) > t table (2.024) and significance (0.014) < 0.05. That is decentralization affect the performance accountability of government agencies. The percentage of the effect of budget goal clarity, accounting controls, reporting systems, and decentralization on accountability for performance by 66,1%.Keywords: Budgeting, Controlling, Accounting, Decentralization And Performance